2018
DOI: 10.3390/cancers10120474
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of TYRO3 as a Therapeutic Target in Cancer

Abstract: The TAM family (TYRO3, AXL, MERTK) tyrosine kinases play roles in diverse biological processes including immune regulation, clearance of apoptotic cells, platelet aggregation, and cell proliferation, survival, and migration. While AXL and MERTK have been extensively studied, less is known about TYRO3. Recent studies revealed roles for TYRO3 in cancer and suggest TYRO3 as a therapeutic target in this context. TYRO3 is overexpressed in many types of cancer and functions to promote tumor cell survival and/or prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 146 publications
(324 reference statements)
1
65
0
3
Order By: Relevance
“…To further figure out the mechanism of circRNA-miRNA-mRNA network, we idetified TYRO3 as one direct target of miR-338-3pin CRC cells. TYRO3 is a protein tyrosine kinase and previous literatures have revealed that TYRO3 is significantly increased in various cancers, promoting cancer cell proliferation and metastasis and enhancing the drug resistance, making it a potential therapeutic target [27,28]. In addition, TYRO3 was also confirmed to play vital roles in the regulation of EMT process, chemical resistance, liver metastasis, cell proliferation and apoptosis in colorectal cancer as an oncogene [29].…”
Section: Discussionmentioning
confidence: 95%
“…To further figure out the mechanism of circRNA-miRNA-mRNA network, we idetified TYRO3 as one direct target of miR-338-3pin CRC cells. TYRO3 is a protein tyrosine kinase and previous literatures have revealed that TYRO3 is significantly increased in various cancers, promoting cancer cell proliferation and metastasis and enhancing the drug resistance, making it a potential therapeutic target [27,28]. In addition, TYRO3 was also confirmed to play vital roles in the regulation of EMT process, chemical resistance, liver metastasis, cell proliferation and apoptosis in colorectal cancer as an oncogene [29].…”
Section: Discussionmentioning
confidence: 95%
“…TYRO3 is a protein tyrosine kinase. Previous literature has shown that TYRO3 is signi cantly increased in various cancers, and it promotes cancer cell proliferation and metastasis and enhances drug resistance, and thus is a potential therapeutic target [27,28]. In addition, TYRO3 was also con rmed to play vital roles in regulating the expression of EMT markers, chemical resistance, liver metastasis, cell proliferation, and apoptosis in CRC as an oncogene [29].…”
Section: Discussionmentioning
confidence: 95%
“…Tyro3TK was initially discovered as a therapeutic target in tumors [36]. Increasing studies have focused on their critical role in autoimmune diseases [37,38].…”
Section: Discussionmentioning
confidence: 99%